PENGARUH PENERAPAN TEKNIK QUICK ON THE DRAW TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 3 HILIRAN GUMANTI KABUPATEN SOLOK - Yeni, Ezi Yolfitra; Nilawasti, Nilawasti; Zulfaneti, Zulfaneti (Pendidikan Matematika, 2013)
ABSTRACTThis research is motivated by the low of students understanding of mathematic concept and monotonesâ students in learning process. The research purpose is how students activity in learning process by applying a quick on the draw technique and whether the students understanding of mathematic concept by applying Â this quick on the draw technique is better than conventional learning in grade VIII SMPN 3 Hiliran Gumanti. This type of research is experimental, research with Â randomization design. The populations are the students of grade Â VIII SMPN 3 Hiliran Gumanti. The sample clasies were determined randomly, which Â is take the grade VIII.A as experimental class and grade VIII.B as control class. The instrument used is this research is observation sheet and concept understanding test with a reliability Â test r11 = 0.89. Based on the result of the observation, by applying quick on the draw technique make the students activity increase. The technique Â of data analysis is using T-test and the result is tcalculated=1,94 and ttable=1,69 with Î±=0,05. So, tcalculated > ttable Â it can conclude that the mathematics concept of students in applying this quick on the draw technique better than the conventional concept in grade VIII SMPN 3 Hiliran Gumanti.